Evaluation of glucose intolerance in adolescents relative to adults with type 2 diabetes mellitus - (:unkn) unknown (Freund Publishing House Ltd, 2006)
Aim: There is an increasing trend in the prevalence of type 2 diabetes mellitus (DM2) in childhood and adolescence, while positive family history of DM2 and obesity are the most important risk factors. To study the influence of family history and obesity on glucose intolerance in our country was the aim of this study. Study design and methods: A total of 105 children and adolescents aged 10-18 years (mean 13.3 ± 2.5 years) were included in the study. All children and adolescents were divided into three groups according to positive family history of DM2 and obesity, and an oral glucose tolerance test (OGTT) was performed for all. Prediabetes was defined as impaired glucose tolerance (IGT) and/or impaired fasting glucose (IFG). Insulin secretion and insulin resistance were estimated using the insulinogenic index; and the homeostatic model assessment for insulin resistance (HOMA-IR) and Matsuda index, respectively. Results: The prevalence of prediabetes was 15.2% in the whole group, while it was 25.5% in obese children who also had a positive family history of DM2. The frequency of hyperinsulinism was 57.1% in all groups. Prediabetic children had significant insulin resistance (HOMA-IR 11.5±7.1 and 4.1 ± 6.4, respectively, p = 0.034). Conclusions: Obesity and glucose intolerance are also a problem in developing countries. The risk of prediabetes in children is highest in obese children who also have a positive family history of DM2. There is a need for a lifelong preventive program starting in childhood to avoid DM2 and decrease cardiovascular risk factors. © Freund Publishing House Ltd., London.
Keywords: Adolescents; Glucose intolerance; Obesity; Oral glucose tolerance test; Prediabetes; Type 2 diabetes mellitus